Culture code the secrets of highly successful groups - Coyle, Daniel (London Random House Business, 2018)
The Culture Code reveals the secrets of some of the best teams in the world - from Pixar to Google to US Navy SEALs - explaining the three skills such groups have mastered in order to generate trust and a willingness to collaborate. Combining cutting-edge science, on-the-ground insight and practical ideas for action, it offers a roadmap for creating an environment where innovation flourishes, problems get solved, and expectations are exceeded.
Keywords: Teams in workplace; Corporate culture; Leadership; Social psychology